2008
DOI: 10.1002/jnr.21774
|View full text |Cite
|
Sign up to set email alerts
|

Pitx3‐transfected astrocytes secrete brain‐derived neurotrophic factor and glial cell line‐derived neurotrophic factor and protect dopamine neurons in mesencephalon cultures

Abstract: The transcription factor Pitx3 is crucial for the development and differentiation of dopamine (DA) neurons. Our previous work has shown the Pitx3 can up-regulate the expression of brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF) in neuroblastoma cell line SH-SY5Y. Primary astrocytes are the major nonneuronal cells and can be easily modified genetically to deliver therapeutic molecules into the brain, so we investigated whether Pitx3 can increase the expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…We have previously shown that overexpression of Pitx3 upregulates the transcription and secretion of BDNF protein from neuroblastoma cells and primary VM as well as astrocyte cultures (Peng et al, 2007;Yang et al, 2008). We therefore hypothesized that GDNF-mediated activation of Pitx3 expression might subsequently induce the transcription of BDNF in these cells.…”
Section: Gdnf-mediated Activation Of Pitx3 Expression Induces Bdnf Trmentioning
confidence: 98%
“…We have previously shown that overexpression of Pitx3 upregulates the transcription and secretion of BDNF protein from neuroblastoma cells and primary VM as well as astrocyte cultures (Peng et al, 2007;Yang et al, 2008). We therefore hypothesized that GDNF-mediated activation of Pitx3 expression might subsequently induce the transcription of BDNF in these cells.…”
Section: Gdnf-mediated Activation Of Pitx3 Expression Induces Bdnf Trmentioning
confidence: 98%
“…On a cell-by-cell basis, Pitx3 immunoreactivity was found in the vast majority of all brainstem dopamine neurons in aged humans, with the intensity of regional mRNA data reflecting the dopamine cell density observed in these regions. Because Pitx3 has been shown to be important for the regulation of the rate-limiting enzyme for dopamine synthesis (Lebel, et al, 2001) and the regulation of neurotrophic factors (including BDNF and GDNF (Yang, et al, 2008) both of which have been trialed as PD therapeutics (Nagahara andTuszynski, 2011,Sullivan andToulouse, 2011)), and of essential microRNAs for neuronal maintenance (Kim, et al, 2007), its continued expression in adult human dopamine neurons is not surprising.…”
Section: On a Cell-by-cell Basis Adult Human Dopamine Neurons Appearmentioning
confidence: 99%
“…Pitx3-transfected astrocytes, carnosic acid, L-theanine, and tripchloride stimulated the secretion of NTFs and attenuated the oxidative damage induced by neurotoxicants in the dopaminergic cells. 36,37,50,55) Earlier, we also found that the present level of induction of these NTFs can afford neuroprotection in some models of neuronal injury (data not shown). Taken together, these observations suggest that the degree of induction of NTF expression found in this study is likely to play a role in neuroprotective mechanisms.…”
Section: ) L-mentioning
confidence: 60%
“…L-Theanine, a green tea component, transcription factor Pitx3, the antiexcitototoxic agent riluzole, the N-methyl-D-asparate (NMDA)-receptor antagonist ifenprodil, and the mood stabilizers valproate, lithium, and anti-Parkinson monoamine oxidase (MAO)-B inhibitor rasagiline, have been found to increase BDNF and GDNF expression in cultured cells and tissues and to support the survival and differentiation of dopamine neurons. 10,37,[49][50][51] Although two NTFs, BDNF and GDNF, were upregulated by RVS, the extent of increase differed between them. The degrees of induction were significantly different at the transcriptional as well as the translational level, but temporal changes were similar among these NTFs at the two levels.…”
Section: ) L-mentioning
confidence: 99%